Contingency-based delay to reinforcement following functional communication training for autistic individuals: A multilevel meta-analysis. (May 2022) - Muharib, Reem; Dowdy, Art; Rajaraman, Adithyan; Jessel, Joshua
Functional communication training, an intervention for challenging behavior rooted in principles of applied behavior analysis, has copious empirical support dating back to the mid-1980s for autistic individuals. Recently, there has been a concerted effort to thin reinforcement delivery during functional communication training using contingency-based delays that, in turn, are designed to enhance practicality and feasibility while not compromising on efficacy. In this synthesis, we meta-analyzed the literature using log response ratio effect sizes to investigate (a) combined and across type effectiveness of contingency-based delays and (b) moderating variables that might impact intervention outcomes. Findings showed that contingency-based delays were effective for autistic individuals (log response ratio = −2.17; 95% CI = (−2.76, −1.58)) and most effective when the contingency incorporated positive reinforcement (log response ratio = −2.30; 95% CI = (−2.83, −1.78)). In addition, delay procedures that included differential reinforcement of alternative behavior were overall more effective (log response ratio = −2.13; 95% CI = (−2.72, −1.55)) than those that involved differential reinforcement of other behavior (log response ratio = −1.24; 95% CI = (−3.84, 1.37)). Noteworthy moderating variables found to impact contingency-based delay efficacy included the intervention dosage and the topography of behavior. We discuss these findings and highlight directions where additional empirical research is warranted to improve our understanding about contingency-based delays for autistic individuals. Lay abstract: Functional communication training, an intervention for challenging behavior rooted in principles of applied behavior analysis, has copious empirical support dating back to the mid-1980s for autistic individuals. Recently, there has been a concerted effort to thin reinforcement delivery during functional communication training using contingency-based delays that, in turn, are designed to enhance practicality and feasibility while not compromising efficacy. In this synthesis, we meta-analyzed the literature base with the goal of investigating both combined and across type effectiveness of contingency-based delays. We also aimed to investigate moderating variables that might impact intervention outcomes. Findings showed that contingency-based delays were effective for individuals with an autism spectrum disorder diagnosis and most effective when the delay incorporated some form of positive reinforcement. In addition, differential reinforcement of alternative-based delays was overall more effective when compared to differential reinforcement of other behavior-based delays. Noteworthy moderating variables found to impact contingency-based delay efficacy included the intervention dosage and the topography of behavior. We discuss these findings and highlight directions where additional empirical research is warranted to improve our understanding about contingency-based delays for individuals diagnosed with autism spectrum disorder.